Research on the anti-synchronization chaos system group ＆large scale distributed system security communication - Guang-ming SUN; Jin-jie HUANG; Qiao LIU (Tongxin xuebao)
Chaotic system model about point group symmetry in the phase space was constructed,and the anti-synchronization problem of the chaotic system group was studied.Besides,a kind of chaotic system group anti-synchronization controller was proposed,and the anti-synchronization of the chaos system group was realized.Through experimental observation,the position of chaos system about the subsystem and the source system after the point symmetry transform changed in phase space.The phase space power trajectory,space topology and other original system presented symmetrical structure.By using the above research conclusions,a kind of carrier communication method of anti-synchronization chaos system group was put forward.It solved the increasingly urgent communication security issues of modern complex distributed and large scale communication system with many access signals and parallel transmission.In addition,with permanent magnet synchronous motor chaos model,simulation and validation were conducted.The experimental results show that the method has good application prospect,and is suitable for modern communication system.